2003
DOI: 10.1177/0013164403251332
|View full text |Cite
|
Sign up to set email alerts
|

Testing Configural, Metric, Scalar, and Latent Mean Invariance Across Genders in Sociotropy and Autonomy Using a Non-Western Sample

Abstract: The Personal Style Inventory (PSI) was developed to assess individuals' levels of sociotropy and autonomy, two personality characteristics considered to be associated with increased vulnerability to depression. This study used the approach of latent means analysis (LMA) within the framework of structural equation modeling (SEM) to explore the factor structure and gender differences associated with the PSI in a sample of Korean undergraduates (N = 508). Results of the confirmatory factor analysis are consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
231
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 446 publications
(236 citation statements)
references
References 50 publications
1
231
0
4
Order By: Relevance
“…Finally, self-efficacy was estimated with two variables derived from previous studies (Duhachek & Iacobbuci, 2005;Rosen & Weil, 1995), which included asking respondents about their levels of knowledge and ability in using mobile phones. As shown in Table 2, skewness and kurtosis statistics of the constructs met the requirements of normal distribution (Hong et al, 2003). The results of the confirmatory factor analysis and Cronbach's α coefficients, for women and men, suggested that all parameters were loaded significantly on their respective latent variables.…”
Section: Methodsmentioning
confidence: 71%
See 3 more Smart Citations
“…Finally, self-efficacy was estimated with two variables derived from previous studies (Duhachek & Iacobbuci, 2005;Rosen & Weil, 1995), which included asking respondents about their levels of knowledge and ability in using mobile phones. As shown in Table 2, skewness and kurtosis statistics of the constructs met the requirements of normal distribution (Hong et al, 2003). The results of the confirmatory factor analysis and Cronbach's α coefficients, for women and men, suggested that all parameters were loaded significantly on their respective latent variables.…”
Section: Methodsmentioning
confidence: 71%
“…SEM has become one of the most popular methods in multivariate analysis; it involves greater theoretical meaningfulness and cross-population stability, by controlling measurement errors and testing for a more complex set of relationships than regression or ANOVA methods do (Kim, Kim, & Hong, 2009;Motl, Dishman, Saunders, Dowda, Felton, Ward, & Pate, 2002;Yuan & Bentler, 2000). And it is important to satisfy the invariance constraints, because multigroup comparisons may be meaningless without measurement invariance, (Hancock, 1997;Hong et al, 2003). As shown in Table 3, we conducted measurement invariance tests sequentially across gender groups, which are the pre-requisites for LMC (Steenkamp & Baumgartner, 1998): (a) configural invariance, (b) metric invariance, and (c) scalar invariance.…”
Section: Tests Of Invariancementioning
confidence: 99%
See 2 more Smart Citations
“…It examines whether there is equality between the measure variable intercepts of the construct (Hair et al, 2010). This implies that the scalar test establishes whether two different groups use a response scale in a similar fashion (Hong et al 2003;Campbell et al 2008). Thus configural invariance, metric invariance, and scalar invariance were conducted to validate the instrument before compare the mean differences between Australian and Chinese public accountants.…”
Section: Methodsmentioning
confidence: 99%